Location discovery for sensor networks with short range beacons. (9th April 2009) - Liu, Fang; Cheng, Xiuzhen; Hua, Dong; Chen, Dechang
In this paper, we present TPSS, a time-based positioning scheme for sensor networks with short-range beacons. By measuring Time Difference of Arrival (TDoA) of signals from nearby beacons, nodes can use TPSS to effectively estimate their locations through trilateration iteratively. We also propose iTPSS as an enhancement to improve the localisation accuracy by a clustering-based position refinement. Extensive simulations have been conducted and the results indicate that both schemes are effective and efficient for location discovery, and iTPSS outperforms TPSS in positioning accuracy.